Osteoprotegerin Levels Decrease During Testosterone Therapy in Aging Men and are Associated with Changed Distribution of Regional Fat - Frederiksen, L.; Glintborg, D.; Højlund, K.; Hougaard, D. M.; Brixen, K.; Rasmussen, L. M.; Andersen, M. (Hormone and Metabolic Research, 2013)
The cardiovascular effects of testosterone treatment are debated. Osteoprotegerin (OPG) is an independent marker of cardiovascular risk. We investigated the effect of testosterone therapy on OPG levels in aging men with low normal bioavailable testosterone levels. A randomized, double-blinded, placebo-controlled study of 6 months testosterone therapy (gel) in 38 men aged 60–78 years with bioavailable testosterone <7.3 nmol/l and waist circumference >94 cm was performed. Clinical evaluation, OPG, and C-reactive protein (CRP) measurements were carried out. Lean body mass (LBM), total fat mass, and bone mineral density (BMD) were established by dual X-ray absorptiometry. Visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) were measured by magnetic resonance imaging. Power calculation was based on an increase in LBM during testosterone therapy and responders were defined as testosterone treated patients with increased LBM (Δ LBM positive), n=14. Data are presented as median (interquartile range). Testosterone therapy decreased total fat mass and SAT, whereas VAT was unchanged (n=38). OPG levels decreased during testosterone therapy (from 2.0 (1.9–2.5) to 1.9 (1.6–2.2) ng/ml, p<0.05 vs. placebo), whereas CRP levels were unchanged (n=38). In responders to testosterone therapy (n=14), ΔOPG levels were inversely associated with ΔSAT (r= − 0.60, p=0.03) and positively associated with ΔVAT (r=0.56, p=0.04). OPG levels decreased during testosterone therapy suggesting decreased cardiovascular risk. Decreased OPG levels were associated with changes in regional fat distribution and future studies are needed to further evaluate the association between OPG and regional fat mass distribution.
Keywords: testosterone; osteoprotegerin; relative hypogonadism; body composition; MRI